A randomized trial of initial warfarin dosing based on simple clinical criteria - Shine, Daniel; Patel, Jeetendra; Kumar, Juhi; Malik, Aamir; Jaeger, Joseph; Maida, Mahamadu; Ord, Linda; Burrows, Grover (Thrombosis and Haemostasis, 2003)
Warfarin induction is accomplished by titrating dosage to coagulation test results. Algorithms can guide this process but not identify the starting dose. We hypothesized that an initial warfarin dose approximating the maintenance value would safely enhance rapidity of induction. In a randomized trial we compared a fixed-dose to a maintenance-dose strategy for beginning warfarin therapy. To predict the maintenance dose among patients with differing warfarin requirements we performed regression analysis on clinical factors derived from chart review. Four community hospitals supplied records for retrospective analysis. The prospective trial was conducted in one, a 350-bed teaching institution. A sample of inpatients anti-coagulated during 1998 formed the development set for retrospective study; a 1999 sample formed the validation set. A one-year trial recruited consecutive eligible inpatients initiated on warfarin. We randomly assigned patients to a first warfarin dose calculated using our regression formula or fixed at 5 mg. All patients’ subsequent doses were determined (as a percentage of initial) from coagulation testing. We compared days to anticoagulation, hospitalized hours, complications, and activity of factor II and protein C in a patient sample at intervals after induction. Weight, age, serum albumin, and presence of malignancy explained 25-30% of variance in maintenance dose. Ninety patients (44 calculated-dose and 46 standard-dose) evaluated in the clinical trial. Mean time to anticoagulation (among patients achieving anticoagulation) was 4.2 and 5.0 days, respectively (p = 0.007). We observed no significant differences in other endpoints. Individualized initial dosing may safely hasten war-farin induction.
Keywords: Warfarin; randomized trials; dosing algorithms